2020
DOI: 10.3390/ijms21218270
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord-Derived CD362+ Mesenchymal Stromal Cells Attenuate Polymicrobial Sepsis Induced by Caecal Ligation and Puncture

Abstract: Mesenchymal stromal cells (MSCs) have a multimodal, immunomodulatory mechanism of action and are now in clinical trials for single organ and systemic sepsis. However, a number of practicalities around source, homogeneity and therapeutic window remain to be determined. Here, we utilised conditioned medium from CD362+-sorted umbilical cord-human MSCs (UC-hMSCs) for a series of in vitro anti-inflammatory assays and the cryopreserved MSCs themselves in a severe (Series 1) or moderate (Series 2+3) caecal ligation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…administration of a distinctive human MSC therapeutic product (CD362-enriched hUC-MSC) in the mouse CLP model of polymicrobial sepsis. Initially, in keeping with recently-reported results for this same MSC product in rat models of bacterial pneumonia and sepsis (23,24), we con rmed the potential for early administration of hUC-MSC to modulate LPS-induced systemic in ammation in mice. In a mouse CLP model of polymicrobial sepsis, however, our results indicated that single doses of hUC-MSC administered i.v.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…administration of a distinctive human MSC therapeutic product (CD362-enriched hUC-MSC) in the mouse CLP model of polymicrobial sepsis. Initially, in keeping with recently-reported results for this same MSC product in rat models of bacterial pneumonia and sepsis (23,24), we con rmed the potential for early administration of hUC-MSC to modulate LPS-induced systemic in ammation in mice. In a mouse CLP model of polymicrobial sepsis, however, our results indicated that single doses of hUC-MSC administered i.v.…”
Section: Discussionsupporting
confidence: 77%
“…In the current study, we performed pre-clinical investigation of the anti-in ammatory effects of CD362selected human umbilical cord-derived MSC (hUC-MSC) in mouse models of sepsis. This surface markerselected hUC-MSC is a novel therapeutic product that has demonstrated evidence of e cacy in rat models of bacterial pneumonia and sepsis when administered early after disease onset (23,24). As a clinical-grade investigational medicinal product (IMP), hUC-MSC is currently undergoing phase I/II trial in patients with moderate to severe acute respiratory distress syndrome (ARDS) due to COVID-19 (NCT03042143).…”
Section: Introductionmentioning
confidence: 99%
“…Other markers, such as Stro-1, CD271, CD362, and ABCB5, are also considered as MSC markers by some researchers and even used for MSC flow sorting (Ning et al, 2011 ; Álvarez-Viejo et al, 2015 ; Ballikaya et al, 2020 ; Gonzalez et al, 2020 ). However, in our review we did not find these antibodies to be as available for other species or as well-demonstrated in the literature as CD29 and CD44.…”
Section: Challenges For Clinical Translation Of Mesenchymal Stromal Cmentioning
confidence: 99%
“…Nonetheless, analysis of serum/plasma and kidney tissue at 48 hours indicated signi cant systemic in ammation and renal injury response. These latter analyses provided the clearest evidence for a modulatory effect of the double-dose hUC-MSC regimen on the severity of polymicrobial sepsis when compared to single-dose administration which, in contrast to results recently reported in a rat CLP model (24), was indistinguishable from the saline-treated CLP group across all indices examined. In particular, the clinically-relevant AKI biomarker, NGAL, proved to be a valuable discriminator of sepsis severity and treatment effect in this model and may be an important biomarker for future clinical trials of cell therapies in sepsis and SA-AKI (29,35).…”
Section: Discussionmentioning
confidence: 48%